Systematics of the Carlia fusca complex (Reptilia: Scincidae) from northern Australia - Donnellan, S. C.; Couper, P. J.; Saint, K. M.; Wheaton, L. (Zootaxa, 2009)
Using a combination of mitochondrial and nuclear genetic markers, karyotypes and morphology, we examine the taxonomy of the Australo-papuan scincid lizard Carlia ‘fusca’ complex in northern Australia, all of which had been assigned previously to C. longipes. Carlia longipes, shows substantial variation in Y chromosome morphology between populations, indeed more than is seen between other species of Carlia. Analyses of the molecular genetic data and morphology demonstrate that populations with different Y chromosomes are two different species and also lead to the recognition of a third species from the Torres Strait. We herein define each of these species, for which previously described names can be applied.